Workers' compensation injury claims of aviation industry worker injuries in Alaska, 2014–2015. Issue 1 (1st January 2020) - Moller, Kyle M.; O'Connor, Mary B.; Lee, Jennifer R.; Lucas, Devin L.; Watson, Joanna R.
ABSTRACT: Aviation operations in Alaska often occur in remote locations and during inclement weather. Limited infrastructure and staff in some locations often requires aviation workers to perform tasks outside of their specific job descriptions. Researchers identified workers' compensation claims as a valuable data source to characterise nonfatal injuries among Alaskan aviation workers. Keyword searches of injury claim narrative fields and industry codes were used to identify potentially aviation-related workers' compensation claims during 2014–2015. These claims were manually reviewed to verify whether aviation related and manually coded according to the US Bureau of Labour Statistics' Occupational Injury and Illness Classification System. There were 875 aviation-related injury claims accepted during 2014–2015. Ramp/baggage/cargo agents incurred the most injuries (35%), followed by mechanics/maintenance workers (15%). Among all workers, Overexertion and Bodily Reaction (40%) was most often cited as the injury event, followed by Contact with Objects and Equipment (28%), and Falls, Slips, Trips (22%). Sprains, strains, tears were the most frequent nature of injury (55%). Cargo/freight/luggage was the most frequent source of injury (24%). The 3 most frequently identified injury event types were responsible for over 90% of all injuries, which indicates that preventive interventions should be directed towards tasks rather than occupational groups.